Remediation of Phenol Using Microorganisms: Sustainable Way to Tackle the Chemical Pollution Menace - Bhattacharya, Amrik; Gupta, Anshu; Kaur, Amarjeet; Malik, Darshan (Current Organic Chemistry, 2018)
Background: Phenol is one of the toxic and persistent organic pollutants, usually present in industrial wastewaters originated from petrochemical, coal, and olive mill processing industries. Dephenolization of phenol-laden industrial wastewater is a necessary requirement before discharge into open environment. Remediation using microorganisms or bioremediation is well thought-out as one of the sustainable methods for decontamination of phenol. However, high phenol concentrations rigorously lower the efficiency of microbial phenol degradation. This is due to substrate inhibition and low growth rate. Thus, there is a need of suitable microbial strain(s) which can effectively degrade such high phenol concentrations. Objective: Numerous microbial strains have been reported for phenol degradation but there are comparatively limited reports on degradation of higher phenol concentrations (>1000 mg L-1) and microbial applicability in dephenolization of real industrial wastewaters. In this review, an overview of microbial phenol degradation is presented with major emphasis on aerobic degradation using bacterial strains. Different methods for improving/enhancing the phenol degradation rate, effects of various physico-chemical factors on degradation process, and mechanisms of degradation form the core of the review. A section on applicability of microbial strains in dephenolization of industrial wastewater and major hurdles encountered during the application process is also highlighted in the study.
Keywords: dephenolization